Analysis of the influence and mechanism of sulfur passivation on the dark current of a single GaAs nanowire photodetector. (24th January 2018) - Chen, Xue; Xia, Ning; Yang, Zhenyu; Gong, Fan; Wei, Zhipeng; Wang, Dengkui; Tang, Jilong; Fang, Xuan; Fang, Dan; Liao, Lei
Abstract: Nanowire photodetectors, which have the advantages of fast response and high photoelectric conversion efficiency, can be widely applied in various industries. However, the rich surface states result in large dark current and can hinder the development of high-performance nanowire photodetectors. In this paper, the influence and mechanism of sulfur surface passivation on the dark current of a single GaAs nanowire photodetector have been studied. The dark current is significantly reduced by about 30 times after surface passivation. We confirm that the origin of the reduction of dark current is the decrease in the surface state density. As a result, a single GaAs nanowire photodetector with low dark current of 7.18 × 10 −2 pA and high detectivity of 9.04 × 10 12 cmHz 0.5 W −1 has been achieved. A simple and convenient way to realize high-performance GaAs-based photodetectors has been proposed.